If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30 = n + -12 Reorder the terms: -30 = -12 + n Solving -30 = -12 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -30 + -1n = -12 + n + -1n Combine like terms: n + -1n = 0 -30 + -1n = -12 + 0 -30 + -1n = -12 Add '30' to each side of the equation. -30 + 30 + -1n = -12 + 30 Combine like terms: -30 + 30 = 0 0 + -1n = -12 + 30 -1n = -12 + 30 Combine like terms: -12 + 30 = 18 -1n = 18 Divide each side by '-1'. n = -18 Simplifying n = -18
| x^3-6x^2=3x-18 | | 8v=20.48 | | 9x+3x=6 | | 13c+c= | | -2.2=c-(-.80) | | x^3-2x^2+18=4x | | -20.7+-10=-30.7 | | 1=a-9 | | 2.56=2x | | 3y-3x=180 | | 2p+7=11p-11 | | 6x^2-7x=24 | | 2x^2-10xy-3x+15y= | | -9+y=6 | | -240=12m | | (7y^6)(2y^9)= | | y=-3+-6x | | 3x-3y=180 | | 7(b+6)-3=46 | | 35=3y | | 4+12x-8x+3=31 | | -32/-3 | | 27y+-6=-3+3y | | 3x+2(-1)-22x+(3+x)=5 | | 8x+35=-3 | | -13=a+3 | | x^2+8x^2=-15x | | 9c=27 | | n/-4=11 | | 9c=20 | | 30(20)-10(1x)=15(1x) | | (-2-6i)-(4-6i)=0 |